Ficus deltoidea aqueous leaves extract abrogates enhanced-oxidative damage in ovariectomized rat models - Farah Wahida Ibrahim, , Aida Farahin Abdullah, Chan Yee Ling, Nurul Farhana Jufri,, Nihayah Mohammad, Nor Fadilah Rajab, (Journal of Applied Pharmaceutical Science, 2021)
The aim of the study is to investigate the potential of Ficus deltoidea aqueous extract in protecting the vital organs of female rats against ovariectomy-induced oxidative stress. The rats were grouped into control intact (normal saline), ovariectomized control (OVX), and ovariectomized rats fed orally with 500 mg/kg F. deltoidea extract (OVX+T). Upon treatment completion, the collected organs were homogenized and measured for malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), catalase (CAT), and glutathione peroxidase (GPx). Serum total cholesterol (TC) was also measured. MDA levels were found to increase in the heart and brain of OVX rats. Ovariectomy caused a decrease in the GSH levels and reduced CAT, SOD, and GPx enzyme activities in the organs of the OVX rats. Ovariectomy also caused an increase in serum TC level. The F. deltoidea leaves extract supplementation not only reduced the MDA levels and increased GSH levels and CAT activities in the selected organs of the OVX+T rats but also decreased the TC level in serum. Glutathione (GPx ) activity was found to be increased only in the heart and kidney of the OVX+T rats. In conclusion, F. deltoidea aqueous extract has the potential to be developed as an antioxidant supplement to protect the vital organs against oxidative damages during the postmenopausal condition.
Keywords: Antioxidant, estrogen, Ficus deltoidea, ovariectomized-rats, oxidative stress, menopause.